Haidar M. Abdul-Nabi Encryption Color Images and Transferring Resulted Values to Text File - Abdul-Nabi, Haidar (University of Thi-Qar Journal of Science, 2019)
With the rapid expansion of computer networks during the past few years, security has . become a crucial issue for modern computer systems. The digital image transferring security also is the most important issues that may be very interested field to study and research. Image encryption has applications in Internet communication, multimedia system, medical imaging, military communication, etc. The proposed method deals with encryption the color image and transfer the resulted values into text file to transfer the image on transmission media in encrypted text file form.